The Role of Traditional Markets in Advancing Maqasid Al-Sharia: A Case Study of Pasar Baru Sungai Dama Samarinda - Jamaida, Nur Riski Amalia; Fajri AF, Muh Shadiqul (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study investigates the role of traditional markets in advancing the objectives of Maqāṣid al-Sharīʿah by conducting a qualitative case study of Pasar Baru Sungai Dama in Samarinda, Indonesia. The research applies a thematic analysis grounded in the five dimensions of Maqāṣid al-Sharīʿah—preservation of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), progeny (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). Data were collected through interviews, field observations, and documentation reviews, and analyzed inductively to identify how market practices align with Shariah-based ethical and economic values. Findings reveal that Pasar Baru supports religious practices, provides safety and hygiene infrastructure, fosters ethical education, accommodates family needs, and enhances financial inclusion. These dimensions demonstrate the capacity of traditional markets to contribute meaningfully to Islamic socio-economic goals beyond mere commerce. The study concludes that with deliberate ethical governance, traditional markets can serve as inclusive Shariah-compliant institutions. Implications for Islamic economics, public policy, and local governance are discussed, with recommendations for broader application and future comparative research.